ChemInform Abstract: Synthesis, Characterization and Optical Properties of NH4Dy(PO3)4. Issue 36 (9th September 2014) - Chemingui, S.; Ferhi, M.; Horchani‐Naifer, K.; Ferid, M.
Abstract Polycrystalline NH4Dy(PO3)4 is grown from a mixture of Dy2O3 and excess (NH4)2HPO4 acting as reactive flux (350 °C, 2 d) and further transformed to Dy(PO3)3 by calcination (800 °C, 2 h).